Estimation of accumulated degree hours-based post-mortem intervals in mammalian and avian model - Mostafa, Md Golam; Shobha, Mst Shahanaz Parvin; Ara, Anjuman; Ahmad, Saadia (Jahangirnagar University Journal of Biological Sciences, 2021)
The post-mortem interval (PMI) of a jungle cat (Felis chaus) and a chicken (Gallus gallus domesticus) were estimated as a mammalian and an avian model, respectively. The estimations were performed adopting the Accumulated Degree Hours (ADH) method using blowfly, Lucilia sericata. The required developmental time from oviposition to the 3rd instar larvae of the blowfly species was considered for the determination of PMI in each of the study. The results revealed that the calculated PMI of jungle cat was 5.29 days. On the other hand, the estimated PMI of the chicken was 2.83 days. The difference of these two PMIs in two different models might be due to the variation of temperatures and other related factors in the development of the larvae of the blowfly species. This study might offer a new approach in the medico-legal investigations with a view to resolving homicide as well as other suspected death of animals including wildlife in Bangladesh. Jahangirnagar University J. Biol. Sci. 9(1 & 2): 49-58, 2020 (June & December)